OBSTACLES TO SUSTAINABLE SECURITY IN THE KURDISTAN REGION USING THE FUZZY DELPHI - Khayati, Chiman (American International Journal of Social Science Research, 2022)
This study aimed to investigate the obstacles to achieving sustainable security in the Kurdistan region. The statistical analysis of data was performed through EXCEL software. Based on the studies’ content analysis, nine obstacles to the Kurdistan region’s sustainable security were finally identified to enter Delphi. The fuzzy Delphi method was used to screen and ensure the importance of the identified indicators and select the final indicators. Experts’ opinions were used to assess the importance of the indicators. In this study, fuzzy triangular numbers were used to fuzzy experts’ views. The first-round results showed that all indicators gained more than 7, and as a result, remained in the evaluation. Based on the second-round results, it was found that the difference of all measures was less than 0.5, and thus Delphi was ended. The DEMATEL results showed that the sum of elements (D) indicated the extent to which that factor influenced other factors in the system. Accordingly, C2 had the greatest impact. The sum of column elements (R) for each factor indicated how that factor was affected by other system factors. Thus, C7 was heavily influenced by other system factors. Based on the horizontal vector (D + R), C2 had the most interaction with other criteria. JEL Classification Codes: A19, B10, B25, C10, C53.